The Dilemma of Central Banking as Illustrated in Recent Literature - Riefler, Winfield W. (Quarterly Journal of Economics, 1936)
Journal Article The Dilemma of Central Banking as Illustrated in Recent Literature Get access Winfield W. Riefler Winfield W. Riefler Institute for Advanced Research Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 50, Issue 4, August 1936, Pages 706–718, https://doi.org/10.2307/1891100 Published: 01 August 1936